The Golgin Tether Giantin Regulates the Secretory Pathway by Controlling Stack Organization within Golgi Apparatus - Koreishi, Mayuko (Public Library of Science, 2013)
Golgins are coiled-coil proteins that play a key role in the regulation of Golgi architecture and function. Giantin, the largest golgin in mammals, forms a complex with p115, rab1, GM130, and soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), thereby facilitating vesicle tethering and fusion processes around the Golgi apparatus. Treatment with the microtubule destabilizing drug nocodazole transforms the Golgi ribbon into individual Golgi stacks. Here we show that siRNA-mediated depletion of giantin resulted in more dispersed Golgi stacks after nocodazole treatment than by control treatment, without changing the average cisternal length. Furthermore, depletion of giantin caused an increase in cargo transport that was associated with altered cell surface protein glycosylation. Drosophila S2 cells are known to have dispersed Golgi stacks and no giantin homolog. The exogenous expression of mammalian giantin cDNA in S2 cells resulted in clustered Golgi stacks, similar to the Golgi ribbon in mammalian cells. These results suggest that the spatial organization of the Golgi ribbon is mediated by giantin, which also plays a role in cargo transport and sugar modifications.